Highly corrosion-resistant stainless steel part and its manufacturing method, heat treatment method for stainless steel part, and rolling bearing and its manufacturing method
By heat-treating martensitic stainless steel in a controlled nitrogen atmosphere, the steel achieves a two-phase mixed structure without ferrite, addressing the corrosion and hardness issues in rolling bearings for severe environments.
Patent Information
- Application Number
- JP2022551526
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-09-25
- Publication Date
- 2025-02-06
- Estimated Expiration
- 2040-09-25
AI Technical Summary
Existing martensitic stainless steels used in rolling bearings suffer from reduced corrosion resistance due to ferrite formation in the surface layer, which compromises both hardness and corrosion resistance, especially in severe environments like strong alkaline disinfectants or seawater.
A high nitrogen atmosphere with a partial pressure of 1000 Pa to 10,000 Pa is used during heat treatment to prevent nitrogen loss, maintaining a two-phase mixed structure of residual austenite and martensite without ferrite, ensuring a hardness of HRC57 or higher and improved corrosion resistance.
The solution achieves a stainless steel part with no ferrite in the surface layer, maintaining high hardness and corrosion resistance, suitable for severe environments, and reduces manufacturing costs by preventing ferrite formation.
Smart Images

Figure 0007627701000005 
Figure 0007627701000006 
Figure 0007627701000007
Abstract
Description
[Technical field]
[0001] The present invention relates to a highly corrosion-resistant stainless steel part having excellent corrosion resistance. [Background technology]
[0002] Generally, in rolling bearings that require corrosion resistance, martensitic stainless steels such as SUS440C are used as bearing materials. However, SUS440C contains 16-18% by weight of chromium to improve corrosion resistance, but also contains a high carbon content of 0.95-1.2% by weight to ensure hardness, which generates a large number of chromium carbides of about 20 μm, so its corrosion resistance is not very high. Therefore, it is not suitable for use in severe corrosive environments such as exposure to strong alkaline disinfectants, seawater, rainwater, etc. In addition, ferritic stainless steels and austenitic stainless steels have better corrosion resistance than martensitic stainless steels, but have low strength. For example, austenitic stainless steels have a hardness of about HRC40 even after cold working, and are rarely used for rolling bearings.
[0003] Therefore, as a martensitic stainless steel that combines high corrosion resistance and high hardness, as shown in Patent Document 1, a stainless steel having high corrosion resistance and high hardness is obtained by adding nitrogen and molybdenum instead of reducing the carbon content. High corrosion resistance martensite with high hardness system Stainless steels have been developed. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] Patent No. 5368887 Summary of the Invention [Problem to be solved by the invention]
[0005] The highly corrosion-resistant martensitic stainless steel disclosed in Patent Document 1 has a large amount of nitrogen dissolved therein, and such a martensitic stainless steel having a large amount of nitrogen dissolved therein is quenched in a vacuum furnace to obtain a desired hardness. Chromium and molybdenum are elements that promote ferrite formation, whereas nitrogen is an austenite stabilizing element and inhibits ferrite formation. Therefore, if nitrogen in the surface layer is removed during vacuum quenching, the nitrogen concentration decreases, weakening the ferrite inhibition effect, and ferrite is formed in the surface layer, so that the desired hardness may not be obtained. The rolling bearing standard JIS B1511:1993 requires that the hardness of the raceway of a rolling bearing be within the range of HRC57 to 65, but the present inventors have confirmed that the hardness of the surface layer (within a depth of approximately 50 μm from the surface) may be less than HRC55 due to ferrite formation.
[0006] In addition, ferrite has a body-centered cubic lattice structure, so the solubility limit of carbon is low. teeth The solubility limit of carbon is only about 0.02% by weight at 727°C. Therefore, in the austenite temperature range When the steel is cooled from the temperature at which it is heated, ferrite begins to precipitate on the surface layer, and carbon is released from the ferrite. This causes carbon to concentrate around the ferrite, forming chromium carbides. The chromium around the ferrite is used for the carbides, creating a chromium-deficient layer, which results in a problem of reduced corrosion resistance around the ferrite.
[0007] The present invention has been made in consideration of the above circumstances, and has an object to provide a highly corrosion-resistant stainless steel part that does not contain ferrite in the surface layer and that achieves both high corrosion resistance and high hardness. [Means for solving the problem]
[0008] The inventors have discovered that by heating and quenching highly corrosion-resistant martensitic stainless steel containing a large amount of dissolved nitrogen to a temperature in the range of 1050 to 1120°C in a nitrogen atmosphere with a nitrogen partial pressure of 1000 Pa or more and less than 10,000 Pa, the dissolved nitrogen is prevented from escaping from the surface layer, and ferrite structure is not formed in the surface layer.
[0009] The present invention has been made based on the above findings, and is a highly corrosion-resistant martensitic stainless steel containing, by weight, 0.35 to 0.43% C, 0.5% or less Si, 0.5% or less Mn, 0.04% or less P, 0.04% or less S, 15 to 17% Cr, 0.1 to 0.3% W, 1.5 to 3.0% Mo, 0.001 to 0.005% B, 0.12 to 0.18% N, and the balance being Fe and unavoidable impurities, and to a depth of 50 μm The matrix structure of the surface layer is made up of retained austenite and martensite. Consists of only This is a highly corrosion-resistant stainless steel part with a two-phase structure and a surface hardness of HRC57 or higher. 。
[0010] In the highly corrosion-resistant stainless steel part of the present invention, the matrix structure of the surface layer of the entire outer surface exhibits a two-phase mixed structure containing retained austenite and martensite, so the area ratio of ferrite in the surface layer is zero, i.e., no ferrite is present. As a result, a high surface hardness of HRC57 or more can be obtained. In addition, since no ferrite is present in the surface layer, carbon does not become concentrated locally, and therefore the formation of a chromium-deficient zone due to the generation of chromium carbides is suppressed, thereby improving corrosion resistance.
[0011] Another feature of the present invention is a rolling bearing in which an outer ring and / or an inner ring are made of the highly corrosion-resistant stainless steel part. Yet another feature of the present invention is an assembly including a plurality of single components, at least one of which is the highly corrosion-resistant stainless steel part.
[0012] Yet another feature of the present invention is a method for heat treating a highly corrosion-resistant stainless steel part, comprising the steps of: preparing an intermediate part made of highly corrosion-resistant martensitic stainless steel containing, by weight, 0.35-0.43% C, 0.5% or less Si, 0.5% or less Mn, 0.04% or less P, 0.04% or less S, 15-17% Cr, 0.1-0.3% W, 1.5-3.0% Mo, 0.001-0.005% B, 0.12-0.18% N, with the balance being Fe and unavoidable impurities; and heating and quenching the intermediate part to a temperature in the range of 1050-1120°C in a nitrogen atmosphere with a nitrogen partial pressure of 1000 Pa or more and less than 10000 Pa. Yet another feature of the present invention is a method for producing a highly corrosion-resistant stainless steel part, comprising the above-mentioned method for heat treating a highly corrosion-resistant stainless steel part.
[0013] Next, the reasons for limiting the components in the present invention will be explained. In the following explanation, "%" means "% by weight" unless otherwise specified.
[0014] C: 0.35~0.43% C is an effective component for ensuring the hardness (wear resistance) of steel parts, but since it is also an austenite-forming element, adding a large amount of it can easily form eutectic carbides, making it more likely to crack. Excessive addition also deteriorates corrosion resistance, so the upper limit was set at 0.43%, at which good corrosion resistance was confirmed. And the lower limit was set at 0.35%, at which no ferrite was formed in the surface layer after heat treatment and a hardness of HRC57 or more was obtained.
[0015] ·Si: 0.5% or less Excessive Si content significantly reduces toughness and is detrimental to hot workability, so a small amount is better, but the content is set at 0.5% or less in consideration of manufacturing costs.
[0016] ·Mn: 0.5% by weight or less Mn is an austenite stabilizing element, and excessive addition increases the amount of retained austenite, which reduces hardness after heat treatment, deteriorates corrosion resistance, and is prone to dimensional changes over time. Therefore, although less Mn is better, the content is set to 0.5% or less in consideration of manufacturing costs.
[0017] ·P:0.04% or less P is an ingredient that precipitates at grain boundaries and causes cold brittleness. To avoid cold brittleness, it is desirable to have as little P as possible. However, the content is set to 0.04% or less in consideration of manufacturing costs.
[0018] ·S: 0.04% or less Since S deteriorates the corrosion resistance and hot workability, the content is set to 0.04% or less.
[0019] Cr: 15~17% Cr is an essential element for stainless steels to obtain high corrosion resistance because it forms a strong non-conductive coating, and a large amount must be added. The results of salt spray tests showed that when the Cr content was below 15%, good corrosion resistance could not be obtained even if the N content was sufficient, as described below, so the lower limit was set at 15%. However, Cr can also be a factor in inhibiting martensite formation by generating ferrite. When the Cr content exceeded 17%, ferrite was generated in the surface layer after quenching, resulting in a decrease in hardness, so the upper limit was set at 17%.
[0020] Mo: 1.5-3.0% Mo has the effect of increasing the solid solubility limit of N, improving corrosion resistance, and improving hardenability. To obtain these effects, it is necessary to add 1.5% or more. However, excessive addition reduces toughness and causes the formation of ferrite near the surface, so the upper limit is set at 3.0%.
[0021] N: 0.12~0.18% N is an extremely effective element for improving the surface hardness and corrosion resistance of martensitic stainless steel after heat treatment. To achieve this effect, the N content must be 0.12% or more. On the other hand, the solid solubility limit at which practical martensitic stainless steel can be produced without blowing (bubbles) in the material using air melting, which is more economical than pressurized melting, was 0.18%, so the upper limit was set at 0.18%. This reduced manufacturing costs.
[0022] B: 0.001% to 0.005% Adding B causes the precipitation of BN, which is effective in improving strength and hardenability, but to obtain this effect, an addition of 0.001% or more is necessary. On the other hand, excessive addition leads to a decrease in toughness, so the upper limit of the addition amount is set to 0.005% or less.
[0023] W: 0.1%~0.3% W is an element that improves corrosion resistance and acts as a solid solution strengthening element, contributing to improved strength. To obtain this effect, the addition of 0.1% or more is necessary. However, excessive addition leads to a decrease in toughness, so the upper limit was set at 0.3%, at which no problem-prone performance was obtained.
[0024] ·Base organization The base structure is preferably a two-phase mixed structure containing 13 volume percent or less of retained austenite and the balance being martensite. By keeping the soft retained austenite to 13 volume percent or less and making the balance martensite, a hardness of HRC57 or more can be ensured. Note that the base structure refers to the structure of the base (matrix) excluding carbides, nitrides, and inclusions. Effect of the Invention
[0025] According to the present invention, it is possible to provide a highly corrosion-resistant stainless steel part that does not contain ferrite in the surface layer and that achieves both high corrosion resistance and high hardness. [Brief description of the drawings]
[0026] [Figure 1]1 is a cross-sectional view showing a rolling bearing according to an embodiment of the present invention. [Diagram 2] FIG. 2 is a cross-sectional view showing an outer ring (A) and an inner ring (B) of a rolling bearing according to an embodiment. [Diagram 3] FIG. 2 is a cross-sectional view showing an example of an outer ring (A) and an inner ring (B) of a rolling bearing according to a comparative example. [Figure 4] FIG. 4 is a cross-sectional view showing an example of an outer ring (A) and an inner ring (B) of a rolling bearing according to another comparative example. [Diagram 5] 1 is a micrograph of a metal structure according to an embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0027] FIG 1 is a cross-sectional view showing a rolling bearing (deep groove ball bearing, assembly) 10 according to an embodiment of the present invention. As shown in FIG 1, the rolling bearing 10 has an outer ring 1 and an inner ring 2 as raceways. A raceway groove 1a having an arc-shaped cross section is formed on the inner peripheral surface of the inner ring 1, and a raceway groove 2a having an arc-shaped cross section is formed on the outer peripheral surface of the inner ring 2. A plurality of balls 3 are arranged at equal intervals along the circumferential direction between the raceway grooves 1a, 2a as rolling elements. The plurality of balls 3 are respectively held in a plurality of pockets of a cage 4. The cage 4 can be made of a resin such as polyamide or polyether ether ketone, or a metal. There is no particular limit to the type of cage 4, and any shape can be selected, such as a crown cage, a machined cage, or a corrugated cage. The cage 4 in FIG. 1 is a crown cage.
[0028] The bearing space 5 between the outer ring 1 and the inner ring 2 is sealed with a metallic seal member 6 (metal shield). The seal member 6 is not limited to a metal shield, and a non-contact or contact type rubber seal can also be used. Grease is filled into the bearing space 5 as a lubricant. The grease used is selected according to the application of the rolling bearing 10. Representative greases include lithium soap grease and urea grease, but are not limited to these.
[0029] The outer ring 1 and the inner ring 2 are formed of highly corrosion-resistant martensitic stainless steel. The outer ring 1 and the inner ring 2 are also subjected to the heat treatment according to the present invention, which includes quenching, subzero treatment, and tempering. The matrix structure of the surface layer over the entire surface of the outer ring 1 and the inner ring 2 is composed of martensite and 13 volume % or less of retained austenite, and no ferrite is formed.
[0030] That is, the area ratio of ferrite in the surface layer over the entire surface of the outer ring 1 and the inner ring 2 is zero. This increases the surface and internal hardness to HRC57 or higher. Note that, depending on the application, high corrosion resistance may be required only for the outer ring or the inner ring. In such cases, the highly corrosion-resistant stainless steel part according to the present invention may be used only for the outer ring or only for the inner ring. For example, in a rolling bearing that supports an automobile sliding door, the outer ring is mainly exposed to rainwater and muddy water, so the outer ring is required to have higher corrosion resistance.
[0031] The balls 3 can be made of metal or ceramics. The rolling elements of the rolling bearing are not limited to spherical balls 3, and the rolling elements can be cylindrical rollers to make the rolling bearing a roller bearing. When the balls 3 are made of metal, the material can be the same highly corrosion-resistant martensitic stainless steel as the outer ring 1 and the inner ring 2. This results in balls 3 that have the same or higher corrosion resistance and hardness as the outer ring 1 and the inner ring 2. However, unless the usage environment is a severe corrosive environment, the balls 3 are protected from rust to some extent by grease, so that bearing steels (e.g. SUJ2) that are less corrosion-resistant than highly corrosion-resistant martensitic stainless steels or conventional martensitic stainless steels for bearings (e.g. SUS440C) may be used.
[0032] Fig. 2 shows the outer ring 1 and inner ring 2 of this embodiment after undergoing the heat treatment according to the present invention. As shown in Fig. 2, no ferrite is generated in the surface layer of the entire surface of the outer ring 1 and inner ring 2 of this embodiment. Meanwhile, Fig. 3 shows the outer ring 1 and inner ring 2 of a comparative example after undergoing the same heat treatment. Ferrite is generated in the surface layer of the entire surface of the outer ring 1 and inner ring 2 of the comparative example. After the heat treatment, the end face, outer cylindrical surface (outer diameter surface), and raceway groove 1a of the outer ring 1, and the end face, inner cylindrical surface (inner diameter surface), and raceway groove 2a of the inner ring 2 are finished by grinding.
[0033] FIG. 4 shows the state after the outer ring and the inner ring of FIG. 3 are subjected to a finishing grinding process to remove the ferrite layer on the surface layer. As shown in FIG. 4, the end face, outer cylindrical surface, and raceway groove 1a of the outer ring 1, and the end face, inner cylindrical surface, and raceway groove 2a of the inner ring 2 are finished by grinding, so the ferrite layer on the surface layer in these parts is removed. However, the ferrite layer remains on the surface layer of the cylindrical surface located axially outside the raceway grooves 1a, 2a, which is not ground during finishing, the seal groove for attaching the seal member 6, and the chamfered part, even after finishing. As mentioned above, the ferrite layer on the surface layer leads to a decrease in corrosion resistance and hardness. Therefore, a rolling bearing using the outer ring 1 and the inner ring 2 as shown in FIG. 4 is not desirable because it leaves behind parts with poor corrosion resistance and hardness. In addition, since the surface of the raceway groove 1a is finished by superfinishing, it is difficult to remove too much to achieve the state shown in FIG. 4, which leads to an increase in manufacturing costs. Therefore, it is important to prevent the formation of a ferrite layer on the surface layer by heat treatment in order to suppress manufacturing costs.
[0034] Next, the heat treatment conditions for obtaining the rolling bearing of the embodiment will be described. After the outer and inner rings are formed by cutting, they are heated to a temperature in the range of 1050 to 1120°C in a heat treatment furnace with a nitrogen atmosphere of nitrogen partial pressure of 1000 Pa or more and less than 10,000 Pa, quenched, and then cooled to a temperature in the range of -30 to -90°C for sub-zero treatment. It is preferable to perform tempering at a temperature in the range of 50 to 200° C. This is because the sub-zero treatment is effective in reducing the amount of retained austenite and increasing hardness.
[0035] Nitrogen partial pressure during quenching If the nitrogen partial pressure is less than 1000 Pa, the nitrogen concentration in the surface layer is reduced during quenching, and ferrite is formed. On the other hand, if the nitrogen partial pressure is 10000 Pa or more, in the case of the martensitic stainless steel according to the present invention, nitrogen is dissolved in the surface layer, and the nitrogen concentration may become too high. The dissolution of nitrogen from the outside increases the amount of residual austenite formed after quenching and tempering, leading to a decrease in tempered hardness. In addition, although the addition of nitrogen produces nitrides, if it is added excessively from the outside, the effect of reducing toughness is greater than the improvement in hardness, promoting brittle fracture.
[0036] Therefore, in order to prevent nitrogen from escaping from the surface layer and to avoid nitrogen from dissolving from the outside, the nitrogen partial pressure is desirably 1000 Pa or more and less than 10000 Pa. In order to obtain such a nitrogen atmosphere, it is preferable to introduce nitrogen gas after reducing the pressure inside the furnace from atmospheric pressure to 200 Pa or less, more preferably 100 Pa or less. If the pressure inside the furnace is sufficiently reduced in this way before introducing nitrogen gas, the amount of gases other than nitrogen gas and moisture can be reduced, and unexpected reactions with the metal can be avoided.
[0037] Quenching temperature If the quenching temperature is less than 1050°C, the formation of martensite by quenching (oil or water quenching) is insufficient, making it difficult to obtain a hardness of HRC57 or more. On the other hand, if the quenching temperature exceeds 1120°C, the prior austenite grains become coarse and carbides are dissolved, making it difficult to obtain a hardness of HRC57 or more. Therefore, the quenching temperature is preferably 1050 to 1120°C.
[0038] The present invention is not limited to the raceways and rolling elements of rolling bearings, but can be applied to any highly corrosion-resistant stainless steel parts used as machine parts such as bolts and nuts. EXAMPLES
[0039] Table 1 shows the component contents in weight percent of the martensitic stainless steel examples and comparative examples. The preferable content ranges of the present invention are also shown as effective ranges.
[0040] 1.Hardness and corrosion resistance investigation By machining a bar material of martensitic stainless steel with the composition shown in Table 1, intermediate parts with an outer diameter of 13 mm, an inner diameter of 11.54 mm, and a height of 4 mm were manufactured. These were then quenched in a heat treatment furnace under the nitrogen partial pressure and quenching temperature conditions shown in Table 1, and then quenched at temperatures of -30 to -90°C. After performing sub-zero treatment by cooling to a temperature range of 150 to 200°C, the specimens were tempered in the temperature range of 150 to 200°C to obtain ring-shaped specimens.
[0041] The hardness of the thus obtained sample was measured at a depth of 20 μm from the surface. The cross section of the sample was mirror-polished and then etched, and the structure of an area 50 μm deep and 100 μm wide from the surface was observed at three points using a metallurgical microscope. The area ratio (area%) of ferrite in each area of 50 μm × 100 μm was calculated by image analysis of the structure photograph shown in FIG. 5, and the average value is shown in Table 1. The amount of retained austenite (retained γ) was determined by measuring the volume ratio (volume%) by X-ray diffraction method using an X-ray stress measurement device (PROTO, model number iXRD).
[0042] Additionally, plates 50 mm long, 20 mm wide, and 2 mm thick were machined from martensitic stainless steel bars with the composition shown in Table 1, and heat treated under the same conditions as above. The samples thus obtained were subjected to a 96-hour neutral salt spray test in accordance with JIS Z2371, and the rating numbers were evaluated based on the rating number method of the JIS Z2371:2015 standard. Corrosion resistance with a rating number of 9.8 or higher was deemed good and rated as "A," while corrosion resistance below 9.8 was deemed insufficient and rated as "B." The above measurement and test results are shown in Table 1, along with the material composition of each sample.
[0043] [Table 1]
[0044] As shown in Table 1, in Examples 1 to 5, all of the component ranges that are essential components of the present invention are satisfied, and the preferred ranges of the nitrogen partial pressure and quenching temperature are also satisfied. As a result, the surface layer portion does not have a zero area ratio of ferrite, and a matrix structure consisting of a two-phase mixed structure containing 8.3 to 12.2 volume % of retained austenite and martensite is formed. In addition, if the major axis of the carbides and inclusions dispersed in the matrix exceeds 10 μm in many cases, it adversely affects the corrosion resistance. In Examples 1 to 5, the major axis of the carbides and inclusions dispersed in the two-phase mixed structure of the matrix is 10 μm or less for 95% or more. Therefore, the rating number indicating the corrosion resistance is 9.8 or more in all of the Examples, and the corrosion resistance is evaluated as "A" (good). Furthermore, the hardness of the surface layer portion is HRC57 or more in all of the Examples, and the hardness of the raceway of the rolling bearing specified in the JIS B1511:1993 standard is satisfied.
[0045] In contrast, in Comparative Example 1, the nitrogen partial pressure during quenching was 1000 Pa, so no ferrite was generated in the surface layer, but the C content was less than 0.35%, so the hardness of the surface layer was HRC55, which did not satisfy the JIS B1511:1993 standard for rolling bearings.In Comparative Example 2, the nitrogen partial pressure during quenching was 2000 Pa, so no ferrite was generated in the surface layer, but the N content was less than 0.12%, so the hardness was only HRC56.
[0046] In Comparative Example 3, the nitrogen partial pressure during quenching was 1000 Pa, the same as in Comparative Example 1, so no ferrite was generated in the surface layer, but the quenching temperature was less than 1050°C, which resulted in insufficient martensite generation and only a hardness of HRC56. In Comparative Example 4, the nitrogen partial pressure during quenching was 2000 Pa, so no ferrite was generated in the surface layer, but the quenching temperature exceeded 1120°C, which resulted in only a hardness of HRC56 due to the coarsening of prior austenite grains and the solid solution of carbides.
[0047] In Comparative Example 5, the nitrogen partial pressure during quenching was only 70 Pa, so the amount of ferrite in the surface layer reached an area ratio of 28% by area, and the hardness was only HRC 51. In Comparative Example 6, the nitrogen partial pressure during quenching was 700 Pa, so the amount of ferrite in the surface layer reached 19% by area, and the hardness was only HRC 52.
[0048] In Comparative Example 7, the amount of ferrite in the surface layer was 6 area % and the hardness was HRC 54, even though the nitrogen partial pressure during quenching was 1000 Pa. This is thought to be because the content of Cr, a ferrite-forming element, exceeded 17% in Comparative Example 7, which resulted in the formation of ferrite in the surface layer after quenching, leading to a decrease in hardness.
[0049] In Comparative Example 8, the amount of ferrite in the surface layer was 4 area % and the hardness was HRC 53, even though the nitrogen partial pressure during quenching was 1000 Pa. This is thought to be because the C content in Comparative Example 8 was less than 0.35%, so austenite was not sufficiently generated and ferrite remained, and because the N content was less than 0.12%.
[0050] In Comparative Example 9, the nitrogen partial pressure during quenching was 2000 Pa and no ferrite was present in the surface layer, but the C content exceeded 0.43%, so the rating number was 7 and it could not be said that the corrosion resistance was sufficient, and the corrosion resistance was evaluated as "B" (inadequate). In Comparative Example 10, the nitrogen partial pressure during quenching was 2000 Pa and no ferrite was formed, but the N content was low at 0.10%, so the rating number was 8 and the corrosion resistance was evaluated as "B".
[0051] In Comparative Example 11, the nitrogen partial pressure during quenching was 2000 Pa, so no ferrite was formed, but the Cr content was low at 14.73%, so sufficient corrosion resistance was not obtained, and the rating number was 8 and the corrosion resistance was evaluated as "B." In Comparative Example 12, the nitrogen partial pressure during quenching was 2000 Pa, so no ferrite was formed, but the Mo content was low at 1.11%, so the rating number was 8 and the corrosion resistance was evaluated as "B."
[0052] For comparison, the composition and test results of SUS440C are also shown in Table 1. As is clear from Table 1, SUS440 has a hardness of HRC57, which is hard enough for use as a rolling bearing, but since its rating number is 5 and its corrosion resistance rating is "B," it is not suitable for use in severe corrosive environments.
[0053] 2. Tissue Observation The following describes in detail the microstructural observations performed on Examples 1 to 3, in which the component contents are within the effective range but no ferrite is present in the surface layer, i.e., the ferrite area ratio is zero, and Comparative Examples 5 and 6, in which the component contents are within the effective range but ferrite is present in the surface layer. Table 2 shows the amount of ferrite in three locations in the surface layer of each sample as ferrite area ratio (area %), and Table 3 shows the average value of the ferrite area ratio at the three locations of each sample and the average value of Rockwell C hardness (HRC) at three locations 20 μm deep from the surface. The numbers to the left of the hyphens on the sample labels in Table 2 ("70" to "7000") indicate the nitrogen partial pressure (unit: Pa) during quenching.
[0054] In the microstructural observation, the cross section of the sample was mirror-polished, etched with nital, and photographed with a metal microscope at three locations in an area 50 μm deep and 100 μm wide from the surface of the surface layer. Ferrite is difficult to etch and appears white, so the area ratio was measured by blackening the area by image processing. Figure 5 shows the microstructural photograph of the surface layer obtained in this way after image processing. For samples 70-1 to 70-3 and samples 700-1 to 700-3, in which the nitrogen partial pressure during quenching was less than 1000 Pa, the upper part of the surface layer is shown black in the microstructural photograph after image processing, and it is clearly seen that ferrite has been generated near the sample surface. For samples in which the nitrogen partial pressure during quenching was 1000 Pa or more, there was no part that was shown black even after image processing, and it is seen that ferrite has not been generated. For each sample, the area ratio of ferrite in the area 50 μm deep and 100 μm wide from the surface was calculated using the microstructural photographs processed in this way, and the average value was taken as the ferrite area ratio in the surface layer of each sample.
[0055] The ferrite area ratio was calculated in the same manner for Comparative Examples 7 and 8. As shown in Table 2, in Comparative Example 5, where the nitrogen partial pressure during quenching was 70 Pa, ferrite was generated in the surface layer at 26 area % or more, and ferrite was generated at 16 to 23 area % at 700 Pa. When the nitrogen partial pressure during quenching was 1000 Pa or more, no ferrite was generated, and the ferrite area ratio was zero. Also, as shown in Table 3, when the nitrogen partial pressure during quenching was 1000 Pa or more, the hardness at a depth of 20 μm from the surface was HRC59 or more. This shows that it is effective to set the nitrogen partial pressure during quenching to 1000 Pa or more in order to prevent ferrite from being generated in the surface layer.
[0056] [Table 2]
[0057] [Table 3]
[0058] 3. Life test Using the materials of Examples 1 to 5 and Comparative Examples 5 to 8 above for the inner and outer rings, single-row deep groove ball bearings were fabricated as test rolling bearings. The outer ring had an outer diameter of 13 mm, an inner diameter of 11.54 mm, and a width of 4 mm, while the inner ring had an outer diameter of 9 mm, an inner diameter of 7 mm, and a width of 4 mm. The balls had a diameter of 1.588 mm and were made of DD400 (martensitic stainless steel, hardness HRC60). A polyamide crown-type cage was used as the cage.
[0059] The outer ring of the test rolling bearing was attached to a holder, and the inner ring was fixed to one end of the shaft. The other end of the shaft was inserted into a pair of rolling bearings in the test device, and the shaft was supported so that it could rotate while being kept horizontal. The shaft was rotated at 5,400 rpm while a radial load of 431 N (44 kgf) was applied vertically to the holder, and the test was continued until the test rolling bearing attached to the holder locked (until the shaft stopped rotating). The locking time was the time elapsed from the start of the test until the test rolling bearing locked, and the average locking time of 10 bearings was used as the evaluation index. The results are shown in Table 4.
[0060] In Table 4, for ease of understanding, the numbers of the rolling bearing examples and comparative examples are the same as the numbers of the material examples and comparative examples. For example, a rolling bearing using the material of Example 1 is called Example 1. In addition, in order to confirm the effect of the ferrite layer, the inner ring and the outer ring of the comparative example are finished with insufficient surface hardness of the raceway surface, in other words, with the ferrite layer remaining on the surface layer. Therefore, the surface layer of the comparative example after the inner ring and the outer ring are finished to the dimensions is in the state shown in Figures 3(A) and (B). In addition, sample numbers 1 to 10 were given to the 10 rolling bearings of each example and each comparative example.
[0061] [Table 4]
[0062] As shown in Table 4, the rolling bearings of Examples 1 to 5 had an average lock time of 46 to 66 hours, whereas the rolling bearings of Comparative Examples 5 to 8, in which ferrite was present in the surface layer, had an average lock time of only 3 to 4 hours. These results confirmed that the rolling bearings of the present invention have a long life because they do not have ferrite in the surface layer and have sufficient hardness. [Industrial Applicability]
[0063] The present invention can be used in the field of highly corrosion-resistant stainless steel parts such as rolling bearings, and is particularly suitable for use in the field of highly corrosion-resistant stainless steel parts used in severe corrosive environments. In the above embodiment, a rolling bearing equipped with a highly corrosion-resistant stainless steel part is illustrated, but the present invention is not limited to this, and the highly corrosion-resistant stainless steel part of the present invention can be used in an assembly used in a particularly severe corrosive environment. [Explanation of symbols]
[0064] Reference Signs List 1...outer ring (highly corrosion-resistant stainless steel part), 1a...raceway groove, 2...inner ring (highly corrosion-resistant stainless steel part), 2a...raceway groove, 3...ball (rolling element), 4...retainer, 5...bearing space, 6...sealing member, 10...rolling bearing (assembly).
Claims
1. A highly corrosion-resistant stainless steel part comprising, by weight, 0.35 to 0.43% C, 0.5% or less Si, 0.5% or less Mn, 0.04% or less P, 0.04% or less S, 15 to 17% Cr, 0.1 to 0.3% W, 1.5 to 3.0% Mo, 0.001 to 0.005% B, 0.12 to 0.18% N, and the balance being Fe and unavoidable impurities, wherein the matrix structure of the surface layer portion extending from the entire outer surface to a depth of 50 μm is a two-phase mixed structure consisting only of retained austenite and martensite, and the two-phase mixed structure contains 15 vol% or less retained austenite, and has a surface hardness of HRC 57 or more.
2. A highly corrosion-resistant stainless steel part as described in claim 1, including a portion that is not subjected to grinding after heat treatment.
3. 3. The highly corrosion-resistant stainless steel part according to claim 1, which has a rating number of 9.8 or more after carrying out a neutral salt spray test according to JIS Z2371 standard for 96 hours.
4. 4. The highly corrosion-resistant stainless steel part according to claim 1, wherein the highly corrosion-resistant stainless steel part is a raceway of a rolling bearing.
5. 5. A rolling bearing having a plurality of rolling elements disposed between an inner ring and an outer ring, wherein at least the outer ring or the inner ring is the raceway ring according to claim 4.
6. A rolling bearing as described in claim 5, wherein the portion that is not ground after the heat treatment includes a cylindrical surface located axially outside the raceway groove of the outer ring or inner ring, and the base structure of the surface layer within a range of 50 μm deep from the outer surface of the cylindrical surface is a two-phase mixed structure including retained austenite and martensite.
7. A rolling bearing as described in claim 5, wherein the portion that is not ground after the heat treatment includes a seal groove formed in at least one of the outer ring or the inner ring, and the base structure of the surface layer in the range from the outer surface of the seal groove to a depth of 50 μm is a two-phase mixed structure including retained austenite and martensite.
8. 5. A rolling bearing comprising an inner ring and an outer ring between which a plurality of rolling elements are arranged, wherein the inner ring and the outer ring are the raceway rings according to claim 4.
9. An assembly including a plurality of individual components, at least one of which is a highly corrosion-resistant stainless steel component according to any one of claims 1 to 4.
10. preparing an intermediate part made of highly corrosion-resistant martensitic stainless steel containing, by weight, 0.35 to 0.43% C, 0.5% or less Si, 0.5% or less Mn, 0.04% or less P, 0.04% or less S, 15 to 17% Cr, 0.1 to 0.3% W, 1.5 to 3.0% Mo, 0.001 to 0.005% B, 0.12 to 0.18% N, and the balance being Fe and unavoidable impurities; Heating and quenching the intermediate part in a nitrogen atmosphere having a nitrogen partial pressure of 1000 Pa or more and less than 10000 Pa to a temperature in the range of 1050 to 1120° C.; A heat treatment method for a highly corrosion-resistant stainless steel part comprising:
11. a sub-zero treatment step of cooling the intermediate part to a temperature in the range of −30 to −90° C. after the quenching; A step of tempering the sub-zero treatment by heating to a temperature in the range of 150 to 200 ° C.; The method for heat treating a highly corrosion resistant stainless steel part according to claim 10, comprising:
12. 12. The method for heat treating a highly corrosion-resistant stainless steel part according to claim 10 or 11, wherein the highly corrosion-resistant stainless steel part is a race of a rolling bearing.
13. A method for producing a highly corrosion-resistant stainless steel part, comprising the method for heat treating a highly corrosion-resistant stainless steel part according to any one of claims 10 to 12.
14. 14. A method for manufacturing a rolling bearing having a plurality of rolling elements disposed between an inner ring and an outer ring, wherein at least the inner ring or the outer ring is manufactured by the method for manufacturing a highly corrosion-resistant stainless steel part as recited in claim 13.
15. A method for heat treating a highly corrosion-resistant stainless steel part according to any one of claims 10 to 12, wherein the pressure inside the furnace is reduced from atmospheric pressure to 200 Pa or less before nitrogen gas is introduced.
Citation Information
Patent Citations
Method of mounting contacts
JP1978068887A
High toughness cold roll excellent in presistance to wear, peeling, and chatter mark under rusting environment
JP1997302449A
High rust resistant drilling trapping screw made of martensitic stainless steel excellent in screwing property and method for quenching the same
JP1998036945A
Drive rivet and its production
JP2000345304A
Martensitic stainless steel and roller bearing
JP2010077525A